Assessment for Learning: How Plagiarism can be used as an Efficient Learning Tool - Morales, Lucía; Soler-Domínguez, Amparo (International Journal of Learning, Teaching and Educational Research, 2015)
There is no doubt that plagiarism is a major source of concern among Higher Education Institutions (HEIs). Academic honesty and integrity practices need to be carefully cultivated to ensure that students understand the seriousness and implications of failing to properly acknowledge the information and resources that they use in their college assignments. This paper explores the importance of complying with ethical standards through a review of the literature in the field, from which a case study was developed using observation techniques to gather the data. A research sample of seventy students registered in their final year of study was considered acceptable to support the analysis. Face-to-face feedback sessions were arranged with students after their work had been reviewed and assessed. The feedback sessions were scheduled individually where there was evidence of poor referencing and writing standards that led to cases of plagiarism, which were then discussed with student concerned. The main research findings indicate that students did not have an understanding of what plagiarism involved and in some instances they failed to acknowledge the existence of a problem in the work presented for assessment. Furthermore, the role of the educator became central to ensure that formative feedback was properly developed to motivate and help students to understand the importance of complying with their institution’s ethical guidelines. The study highlights the need to consider cases of plagiarism as another learning tool that contributes to the students’ formation. By developing assessments for learning, the punitive aspect of the assessment process should be kept to a minimum and educators should focus their attention on how plagiarism cases can be used as an efficient learning tool.